Studies on Seminal Enzyme (GOT, GPT and LDH) Profile and its Relationship with Acrosomal Integrity in Surti Buffalo Bull Semen - SHARMA, RAJEEV; PAREEK, P K; TAILOR, S P; PUROHIT, G N (The Indian Journal of Animal Reproduction, 2003)
Six ejaculates each from 5 Surti buffalo bulls were cryopreserved and studied before and aftercryopreservation and at½, 1 and 2 hours post thawing to evaluate the extent of damage of spermatozoa.The sperm motility and percent live sperms and percent normal acrosomes showed a decline aftercryopreservation. The seminal enzymes GOT, GPT and LDH increased in the seminal plasma tosignificanly high level (P
Keywords: Acrosome; GOT; semen; seminal enzymes